OP0104 THE PRESENCE OF BLOOD IN THE JOINT AND THE IMMEDIATE MOLECULAR RESPONSE IN SYNOVIAL FLUID ARE INDEPENDENTLY ASSOCIATED WITH WORSE CLINICAL OUTCOMES AT 2 YEARS AFTER HUMAN KNEE INJURY. (June 2019) - Garriga, Cesar; Goff, Megan; Leyland, Kirsten; Paterson, Erin; Hrusecka, Renata; Hamid, Benjamin; Honeyfield, Lesley; Satchithananda, Keshthra; Lim, Adrian; Arden, Nigel; Judge, Andrew; Williams, Andy; et al.
Abstract : Background: Knee injury increases the risk of knee osteoarthritis at least 7 fold. We have shown an immediate inflammatory response to acute knee injury which is measurable both in mouse joint tissues and also in human synovial fluid (SF). Objectives: We set out to test whether the measured immediate inflammatory protein response in SF or plasma/serum was associated with knee symptoms at 2 years after knee injury. Methods: 150 individuals were recruited within 8 weeks of a significant acute knee injury to the Knee Injury Cohort at the Kennedy (KICK; REC 10/H0805/39; NCT02667756 ) from 2011-2014. The primary outcome was the Knee Injury and Osteoarthritis Outcome Score (KOOS)-4 at 2 years (a composite measure of 4 KOOS domains, where 100 is normal knee health). Baseline covariates were sex, age, body mass index (BMI), clinical effusion, SF blood staining, radiographic Kellgren/Lawrence (KL) Grade. 14 SF and 4 plasma/serum biomarkers were defined based on our prior translational studies. Regression models assessed association of biomarkers with 2 year KOOS4, adjusting for significant covariates. Results: 123/150 (82%) were male, mean age (SD) 27(8) years and BMI 26(4) kg/m 2 . Mean KOOS4 increased from 38(18) at baseline to 70(18) at 2 years. 64 (43%) had KL 0/1, 24 (16%) KL 2 and 11 (7%) KL 3, 75 (50%) medium/large effusion and 50 (39%) moderate/severe SF blood staining. Medium/large knee effusion (-7.2(-13.5, -0.9)P=0.025) and moderate/severe SF blood staining (-10.1(-18.6, -1.6)P=0.02) were significant. Significant biomarkers adjusted for these covariates are shown in Table. MCP-1 and IL-6 were each significantly associated with 2 year KOOS4 independently in the fully adjusted model and in the multivariable model. Conclusion: Those with higher levels of SF MCP-1 and IL-6 at the time of injury had a significantly worse outcome at 2 years. The presence of haemarthrosis, clinical effusion and impairment/pain at the time of injury were also independent predictors of outcome. In contrast, no baseline plasma/serum markers were associated with outcome. Stratifying individuals at high risk of persistent symptoms after knee injury may enable clinical trials of interventions to prevent or treat PTOA. Disclosure of Interests: Cesar Garriga: None declared, Megan Goff: None declared, Kirsten Leyland: None declared, Erin Paterson: None declared, Renata Hrusecka: None declared, Benjamin Hamid: None declared, Lesley Honeyfield: None declared, Keshthra Satchithananda: None declared, Adrian Lim: None declared, Nigel Arden Grant/research support from: Grants from BIOIBERICA, and from MERCK., Consultant for: Personal fees from Flexion, from Regeneron, from Freshfields Bruckhaus Deringer, outside the submitted work., Andrew Judge Grant/research support from: Consortium research grants from Roche, Consultant for: Received consultancy fees, lecture fees and honoraria from Servier, UK Renal Registry, Oxford Craniofacial Unit, IDIAP Jordi Gol and Freshfields Bruckhaus. Member of Deringer Data Safety and Monitoring Board for Anthera Pharmaceuticals, Inc. Consultancy for Freshfields Bruckhaus Deringer, Andy Williams: None declared, Tonia Vincent: None declared, Fiona Watt Grant/research support from: Pfizer and Astellas clinical study grants (not in this area)